Green Synthesis, Characterization and Study of Physical Properties of New Nanocomposite and Used as Adsorbent Surface and Photocatalyst for Waste Water Treatment - Hashim, Afrah; Sabbar, Walaa Jubair; Al-Abodia, Entisar E. (Stallion Journal for Multidisciplinary Associated Research Studies, 2024)
Article including, fabrication of a greatly effective catalyst consisting of ZnFG nanocomposite was studied using an in situ preparation method from specific weights of ZnO and iron oxide nanoparticles, as well as reduced graphene oxide. The effectiveness of fabricated composite as a photocatalytic surface was studied by applying it in advanced oxidation processes (AOP) to degrade methyl orange (MO) dye under sunlight. A high photodegradation efficiency of the dye was reached, about 85%, within 600 minutes. Photocatalysis experiments were conducted using multiple parameters such as time and temperature. The improvement in high photocatalytic activity of a prepared composite can be attributed to increased visible light absorption, reduced the band gap, and effective charge transfer between components. It was also observed that the ZnFG composite exhabited more stability even after repeated photocatalytic procedures, indicating repeated synergistic effects. It is possible that this kind of material can be applied as an efficient and stable photocatalyst for removing pollutants of various types.